2007
DOI: 10.1093/jpepsy/jsm009
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parental Monitoring in Adolescent Health Outcomes: Impact on Regimen Adherence in Youth with Type 1 Diabetes

Abstract: Close parental monitoring of care completion can contribute to better adherence in adolescents with diabetes. General warmth and support in the absence of careful parental supervision may be insufficient to help youth achieve adequate levels of adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
211
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 214 publications
(235 citation statements)
references
References 53 publications
17
211
2
3
Order By: Relevance
“…The findings that part of the benefit of warm and accepting parental relationships for diabetes outcomes occurs through parental monitoring are consistent with those of Ellis et al (9). Ellis et al also found that when monitoring and acceptance were both used to predict diabetes outcomes, only monitoring remained as a significant predictor.…”
Section: Methodssupporting
confidence: 86%
See 4 more Smart Citations
“…The findings that part of the benefit of warm and accepting parental relationships for diabetes outcomes occurs through parental monitoring are consistent with those of Ellis et al (9). Ellis et al also found that when monitoring and acceptance were both used to predict diabetes outcomes, only monitoring remained as a significant predictor.…”
Section: Methodssupporting
confidence: 86%
“…For instance, an adolescent could manage diabetes care tasks independently (low parental involvement), while the parent monitors the success of those independent efforts (high parental monitoring). The benefits of warm and accepting relationships may be due in part to accepting parents being positioned to monitor their adolescent's diabetes activities (9).…”
mentioning
confidence: 99%
See 3 more Smart Citations